2009
DOI: 10.1242/jeb.028738
|View full text |Cite
|
Sign up to set email alerts
|

Functional consequences of structural differences in stingray sensory systems. Part II: electrosensory system

Abstract: SUMMARY Elasmobranch fishes (sharks, skates and rays) possess highly sensitive electrosensory systems, which enable them to detect weak electric fields such as those produced by potential prey organisms. Different species have unique electrosensory pore numbers, densities and distributions. Functional differences in detection capabilities resulting from these structural differences are largely unknown. Stingrays and other batoid fishes have eyes positioned on the opposite side of the body from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
(35 reference statements)
1
25
0
1
Order By: Relevance
“…Montgomery and Skipworth determined that the voltage gradient generated by the weak water jets used in their study could be 1nVcm -1 , which was considered below the electrosensory detection threshold of elasmobranchs (Montgomery and Skipworth, 1997). Kajiura and Holland (Kajiura and Holland, 2002) and part II of the present study (Jordan et al, 2009) have since demonstrated sensitivity well below 1 nV cm -1 for species of sharks and rays; thus, this possibility cannot be ruled out. Unfortunately there was no reasonable way to prevent this byproduct of flow in seawater.…”
Section: Body Positionmentioning
confidence: 61%
“…Montgomery and Skipworth determined that the voltage gradient generated by the weak water jets used in their study could be 1nVcm -1 , which was considered below the electrosensory detection threshold of elasmobranchs (Montgomery and Skipworth, 1997). Kajiura and Holland (Kajiura and Holland, 2002) and part II of the present study (Jordan et al, 2009) have since demonstrated sensitivity well below 1 nV cm -1 for species of sharks and rays; thus, this possibility cannot be ruled out. Unfortunately there was no reasonable way to prevent this byproduct of flow in seawater.…”
Section: Body Positionmentioning
confidence: 61%
“…To date, no sexual differences have been found in the electrosensitivity of elasmobranchs during prey detection trials [Kajiura and Holland, 2002;Jordan et al, 2009], de- (5 -8) (6 -10) (1,800 -2,520) (3,845 -6,152) (738 -1,230) (6,383 -9,902) Values in parentheses are min-max. Also included is an estimate of the total number of nerve axons, and the observed total number of nerve axons, associated with the dorsal root of the ALLN.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the sensitivity of P. motoro to bioelectric fields, a behavioural assay was employed following methods described in similar studies (Kajiura and Holland 2002;Kajiura 2003;Jordan et al 2009;McGowan and Kajiura 2009). An opaque acrylic plate, 2 m in diameter, was placed on the bottom of a 3785-L fibreglass experimental tank at the FWC laboratory.…”
Section: Methodsmentioning
confidence: 99%